Conserving the Kumaun Forests through People's Participation: a Case Study - Mishra, Rajeev (Indian Forester, 1997)
Conserving our forest wealth through peoples participation is the need of the hour. Concept of Van Panchayats in U.P. is very old. These Van Panchayats in U.P. have been managing their forests on sustainable basis. This paper deals with some interesting and successful Van Panchayats in Kumaun hills. It also brings out the problems faced by them and some other important issues that need attention.